2013
DOI: 10.1099/mic.0.069922-0
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic system for expression of components of a bacterial microcompartment

Abstract: In general, prokaryotes are considered to be single-celled organisms that lack internal membrane-bound organelles. However, many bacteria produce proteinaceous microcompartments that serve a similar purpose, i.e. to concentrate specific enzymic reactions together or to shield the wider cytoplasm from toxic metabolic intermediates. In this paper, a synthetic operon encoding the key structural components of a microcompartment was designed based on the genes for the Salmonella propanediol utilization (Pdu) microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…To date, the predictions have been functionally verified for the AldDH of the Haliangium ochraceum BMC [50] and of PduD [71][72][73][74]. The predicted helical conformation has also been confirmed [74].…”
Section: Reviewmentioning
confidence: 82%
See 1 more Smart Citation
“…To date, the predictions have been functionally verified for the AldDH of the Haliangium ochraceum BMC [50] and of PduD [71][72][73][74]. The predicted helical conformation has also been confirmed [74].…”
Section: Reviewmentioning
confidence: 82%
“…Based on this observation and considering that shell proteins are the unifying features of all BMCs, similar peptides mediating the association of proteins with shells were predicted for ten different types of BMC loci through the identification of their shared sequence features: namely, a region of 15-20 amino acids predicted to form an amphipathic a-helix separated from the functional domain(s) of the protein by a poorly conserved linker [15]. To date, the predictions have been functionally verified for the AldDH of the Haliangium ochraceum BMC [50] and of PduD [71][72][73][74]. The predicted helical conformation has also been confirmed [74].…”
Section: Reviewmentioning
confidence: 99%
“…Hence, the possibility that there may be some variation in the assembly requirements, even of closely related MCP systems, should be considered. In more recent studies, the Salmonella pdu genes were also used to produce synthetic MCPs and compartmentalize specific proteins (188). In these studies, vectors for expression of nonnative cargo proteins were constructed, and Western blots as well as an in vivo protease accessibility assay were used to evaluate encapsulation.…”
Section: Heterologous Expression Of Bacterial Mcpsmentioning
confidence: 99%
“…Because the lumen components were not transferred in the latter study, the compartments are hollow, leaving the opportunity for them to be filled with alternate cargo, as discussed below. Pdu compartments from Salmonella entericum have also been made in E. coli (Sargent et al 2013), and empty Eut shells have been reported to form in E. coli as well (Choudhary et al 2012). Finally, a carboxysomes from Halothiobacillus neapolitanis have been expressed in E. coli from a single operon (Bonacci et al 2012).…”
Section: Microcompartmentsmentioning
confidence: 99%